KINERJA CAMPURAN SAMI-R MENGGUNAKAN KARET SERUTAN 10%, 20% DAN 30% BERDASARKAN UJI MARSHALL - Erik Astrawan; Edward Ngii; Rini Sriyani (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2017)
Abstract The results of this research show that the value of the stability of the third draft of specification variation Latasir value obtained above 200 kg. The value for the flow of the third draft variation no one specification with a value between 2-3 mm. The results obtained for the Marshall value Quotient (MQ) in variation II for different types of asphalt levels of specifications. Latasir. For the value of the percentage of The Aggregat Minral Voide (VMA) for the third draft the variation vercentage value obtained above 20%, so that the third draft of the variations can meet the specification. Retrieved value Void Filled With Asphalt (VFWA) on the draft variation II with asphalt levels 10%, 11% and 12% by value of VFWA percentage above 75%. While the value of the Void In The Mix (VIM) obtained on the draft Variation I in asphalt levels 12% with the highest percentage of 5,39%, thus entered in the specification of the latasir with the value of the percentage of VIM between 3-6%.